2021
DOI: 10.3390/ijerph18094900
|View full text |Cite
|
Sign up to set email alerts
|

First Responder Resiliency ECHO: Innovative Telementoring during the COVID-19 Pandemic

Abstract: The First Responder ECHO (Extension for Community Outcomes) program was established in 2019 to provide education for first responders on self-care techniques and resiliency while establishing a community of practice to alleviate the enormous stress due to trauma and substance misuse in the community. When the SARS-CoV-2 (COVID-19) pandemic hit the United States (US) in March 2020, a tremendous strain was placed on first responders and healthcare workers, resulting in a program expansion to include stress mitig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…Furthermore, the present findings provide further support and extend the findings of both Katzman et al ( 2021 ) and Lewis et al ( 2014 ). More precisely, these studies reported significant benefits from PFA training in police officers: significantly increased confidence on providing PFA, competence in providing help in traumatic events, increased PFA knowledge, and self-care practicing were reported (Katzman et al 2021 ; Lewis et al 2014 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Furthermore, the present findings provide further support and extend the findings of both Katzman et al ( 2021 ) and Lewis et al ( 2014 ). More precisely, these studies reported significant benefits from PFA training in police officers: significantly increased confidence on providing PFA, competence in providing help in traumatic events, increased PFA knowledge, and self-care practicing were reported (Katzman et al 2021 ; Lewis et al 2014 ).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the present findings provide further support and extend the findings of both Katzman et al ( 2021 ) and Lewis et al ( 2014 ). More precisely, these studies reported significant benefits from PFA training in police officers: significantly increased confidence on providing PFA, competence in providing help in traumatic events, increased PFA knowledge, and self-care practicing were reported (Katzman et al 2021 ; Lewis et al 2014 ). In the present study, trained police officers were compared to a control group, which received no training in order to control for influences of other variables, mainly the influences of questionnaire re-administration.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Equipped with high-standard internet connectivity, the Smart Pod functionality can also include components of telemedicine and telementoring to provide guidance and education to frontline community healthcare workers. Telementoring, by models such as Project ECHO [48,49], allowed for highly motivating, interactive sessions on the latest best practices, which were especially critical during a pandemic with rapidly changing guidance around COVID-19 testing, management, vaccine administration. Smart Pod healthcare workers were able to implement best practices and be able to counsel patients with new information as it emerged in the literature, especially as challenges such as vaccine hesitancy arose.…”
Section: Discussionmentioning
confidence: 99%